SimuS: A Simulator for Teaching Computer Architecture - Silva, Gabriel P.; Borges, José Antônio dos S. (International Journal of Computer Architecture Education, 2016)
This paper introduces the SimuS simulator, developed for a hypothetical Sapiens processor architecture, specifically designed for teaching computer architecture, based on the experience gained from using and developing the Neanderwin simulator for the Neander-X processor. In the hypothetical Sapiens processor, the architecture and instruction set initially proposed for the Neander-X processor are extended to create a processor architecture with more resources, allowing its use from introductory courses to more advanced ones.